Electrolyte of aqueous zinc-iodine battery, preparation method of electrolyte and aqueous zinc-iodine battery with wide temperature range and high capacity

By using an electrolyte composed of I+ stabilizer, hydrogen bond ligand, low freezing point hydrogen donor solvent and zinc salt in aqueous zinc-iodine batteries, the problems of insufficient energy density and limited temperature range of traditional batteries are solved, and zinc-iodine batteries with high energy density and cyclic stability in a wide temperature range are achieved.

CN119542573AInactive Publication Date: 2025-02-28HEFEI WATER DEPARTMENT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411722102.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional water-based zinc-iodine batteries have insufficient energy density and limited operating temperature range, making it difficult to meet practical application needs.

Method used

An electrolyte consisting of I+ stabilizer, hydrogen bond ligand, low freezing point hydrogen donor solvent and zinc salt is prepared by adjusting the molar ratio and selecting suitable substances, which can work stably in a wide temperature range.

Benefits of technology

The excellent cycle performance of zinc-iodine batteries in the temperature range of -25℃~40℃ is achieved, the energy density and cycle stability of the battery are improved, and the operating temperature range of the battery is broadened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542573A_ABST
    Figure CN119542573A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte of an aqueous zinc-iodine battery, and relates to the technical field of zinc-iodine batteries, the electrolyte is prepared from an I + stabilizer, a hydrogen bond ligand, a low-freezing-point hydrogen donor solvent and a zinc salt, and the molar ratio of the I + stabilizer to the hydrogen bond ligand to the low-freezing-point hydrogen donor solvent to the zinc salt is 1: 0.5: 5: 0.5-1.5. The invention also provides a preparation method of the electrolyte and a zinc-iodine battery prepared by using the electrolyte. The zinc-iodine battery constructed by the invention can realize highly reversible I- / I2 / I + conversion and rapid iodide conversion kinetics in a wide temperature range of-25 DEG C to 40 DEG C, and has high energy density and excellent long cycle stability. In addition, due to the unique solvation structure of the electrolyte, the activity of water molecules in the system is reduced, and then the hydrogen evolution reaction and other side reactions are inhibited. Therefore, the invention provides a feasible strategy for realizing wide temperature range, high capacity and high performance of the zinc-iodine battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zinc-iodine batteries, and in particular to an electrolyte for an aqueous zinc-iodine battery and a preparation method thereof, and an aqueous zinc-iodine battery with a wide temperature range and high capacity. Background Art

[0002] Aqueous zinc iodine (Zn-I 2 As an emerging electrochemical energy storage technology, ) batteries have attracted extensive attention from researchers due to their fast redox kinetics, low cost, high discharge voltage platform and high safety. 2 / I - Two-electron aqueous Zn-I 2 The battery voltage is only about 1.3V, and the energy density is low, which is difficult to meet the needs of practical applications. In recent years, due to the redox reaction of iodine-rich, the work of activating high-valent iodine reaction to achieve high-potential aqueous zinc-iodine batteries has been reported one after another. This kind of work mainly uses electrolyte design to anchor I + Implementation I - / I 2 / I + The four-electron reaction realizes an aqueous zinc-iodine battery with high potential and high theoretical specific capacity.

[0003] However, this design often requires a higher free halogen ion concentration to achieve stable I + Ions, and a large number of free halogen ions will cause serious damage to the surface of the zinc negative electrode due to pitting, resulting in problems such as corrosion, hydrogen evolution, and dendrite growth, and will also corrode the remaining components of the battery. Especially when the aqueous zinc-iodine battery is operated under high temperature conditions, the above problems will be further aggravated, thus seriously affecting the cycle stability of the whole battery; on the other hand, in a low temperature environment, the slow ionic conductivity also leads to poor battery performance.

[0004] It can be seen that the above problems greatly limit the operation of aqueous zinc-iodine batteries. In order to overcome these limitations, it is critical to activate the multivalent iodine conversion reaction with higher reaction potential and improve the electrolyte to broaden the operating temperature range of zinc-iodine batteries. In addition, in traditional aqueous electrolyte systems, I + It is highly unstable and tends to be hydrolyzed or kinetically redox-produced by I 3- Therefore, it is necessary to explore the rapid and reversible I - / I 2 / I + Aqueous zinc electrolytes for conversion and stabilization of zinc anodes are essential for achieving high energy density Zn-I 2 Full batteries are of great significance. Summary of the invention

[0005] The invention discloses an electrolyte for an aqueous zinc-iodine battery and a preparation method thereof, and an aqueous zinc-iodine battery with a wide temperature range and high capacity, which can solve the problems of insufficient energy density and limited operating temperature range of existing aqueous zinc-iodine batteries.

[0006] The technical solution adopted by the present invention is as follows:

[0007] One of the objects of the present invention is to provide an electrolyte for an aqueous zinc-iodine battery, comprising: + The invention is prepared from a stabilizer, a hydrogen bonding ligand, a low freezing point hydrogen donor solvent and a zinc salt, wherein the + The molar ratio of the stabilizer, the hydrogen bonding ligand, the low freezing point hydrogen donor solvent and the zinc salt is 1:0.5:5:0.5-1.5.

[0008] Preferably, the I + The molar ratio of the stabilizer, the hydrogen bonding ligand, the low freezing point hydrogen donor solvent and the zinc salt is 1:0.5:5:1.5.

[0009] Preferably, the I + The stabilizer is choline chloride or choline bromide.

[0010] Preferably, the hydrogen bonding ligand is urea.

[0011] Preferably, the zinc salt is zinc sulfate heptahydrate.

[0012] Preferably, the low freezing point hydrogen donor solvent is at least one of methanol, ethylene glycol and glycerol.

[0013] The second object of the present invention is to provide a method for preparing the above-mentioned electrolyte, comprising the following steps:

[0014] Step 1: Weigh I according to the proportion + The stabilizer, hydrogen bonding ligand, and zinc salt are placed in a beaker, and a low freezing point hydrogen donor solvent is added to obtain a mixed solution, which is then stirred at 60-70°C for 1-2h and then cooled to room temperature;

[0015] Step 2: Add 40-60% by volume of deionized water to the mixed solution obtained in step 1, and ultrasonicate at room temperature until the solution is uniform and transparent, thereby obtaining an electrolyte.

[0016] The third object of the present invention is to provide a wide temperature range, high capacity aqueous zinc-iodine battery, comprising a positive electrode, a negative electrode, a separator and the above-mentioned electrolyte.

[0017] Preferably, the positive electrode is a composite material of iodine and activated carbon.

[0018] Preferably, the negative electrode of the battery is metallic zinc.

[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0020] (1) The present invention is based on I + A new electrolyte system is synthesized through the interaction of stabilizers, hydrogen bonding ligands, low freezing point hydrogen donor solvents and zinc salts. It is not only simple in preparation method and operation process, low in cost, safe and environmentally friendly, but also convenient for large-scale industrial production.

[0021] (2) In the process of preparing the electrolyte of the present invention, based on the reaction sequence of the substances, the hydrogen bonding ligand forms a hydrogen bond with the zinc salt first, promoting the dissolution of the zinc salt; then the low freezing point hydrogen donor solvent destroys the H 2 The hydrogen bond network between O molecules can change the hexahydrate coordination solvation structure of zinc and reduce the 2 O molecules, thereby inhibiting the side reactions related to the zinc negative electrode; on the other hand, H 2 The reduction in the activity of O molecules also lowers the overall freezing point of the electrolyte, which can effectively broaden the operating temperature range of the aqueous zinc-iodine battery and enable the aqueous zinc-iodine battery to have excellent cycle performance in the temperature range of -25°C to 40°C.

[0022] (3) In the process of preparing zinc-iodine battery of the present invention, the nucleophilic Cl - The electrophilic iodide ion (I + ) to form a stable I-Cl compound, which can effectively inhibit I + Hydrolysis of positive ions; using Ch + The catalytic effect can promote the four-electron conversion reaction kinetics of iodine molecules, thereby effectively solving the high output voltage and capacity that are difficult to achieve in zinc-iodine batteries, and improving the energy density and cycle stability of zinc-iodine batteries.

[0023] (4) The various links of the present invention are closely linked and complementary to each other. Through the clever selection of materials and the ratio between the materials, combined with an effective preparation method, a feasible strategy is provided for achieving a wide temperature range, high capacity and high performance of zinc-iodine batteries, which is very suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The charge and discharge curves of the zinc-iodine batteries obtained in Example 9 and Example 10 of the present invention are shown respectively.

[0025] Figure 2 The charge and discharge curves of the zinc-iodine batteries obtained in Example 9 and Examples 11 and 12 of the present invention are shown.

[0026] Figure 3 The cyclic voltammetry curves of the zinc-iodine batteries obtained in Example 9 of the present invention and Comparative Examples 3 and 4 are shown respectively.

[0027] Figure 4 The charge and discharge curves of the zinc-iodine batteries obtained in Example 9 of the present invention and Comparative Examples 3 and 4 are shown respectively.

[0028] Figure 5 This is a cycle performance diagram of the zinc-iodine battery obtained in Example 9 of the present invention at room temperature and a current density of 10C.

[0029] Figure 6 This is a cycle performance diagram of the zinc-iodine battery obtained in the present invention-Comparative Example 2 at room temperature and a current density of 10C.

[0030] Figure 7 This is a cycle performance diagram of the zinc-iodine battery obtained in Example 9 of the present invention at 40°C and a current density of 10C.

[0031] Figure 8 This is a cycle performance diagram of the zinc-iodine battery obtained in Example 9 of the present invention at -25°C and a current density of 0.5C.

[0032] Fig. 9 The cycling performance diagram of the Zn||Zn symmetric battery assembled using the electrolytes in Examples 1, 4, and 5 at room temperature.

[0033] Fig.10 This is a long cycle performance diagram of a Zn||Zn symmetric battery assembled using the electrolyte in Example 1 at 40°C.

[0034] Fig.11 This is a long cycle performance diagram of the Zn||Zn symmetric battery assembled using the electrolyte in Example 1 at -25°C. DETAILED DESCRIPTION

[0035] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with various embodiments.

[0036] Example 1

[0037] This embodiment provides an electrolyte for preparing an aqueous zinc-iodine battery. The electrolyte is composed of I + The invention is prepared from a stabilizer, a hydrogen bonding ligand, a low freezing point hydrogen donor solvent and a zinc salt, wherein I + The role of the stabilizer is to activate the four-electron reaction; the role of the hydrogen-bonding ligand is to form hydrogen bonds with the zinc salt; the role of the low-freezing-point hydrogen donor solvent is to destroy the hydrogen-bonding network between water molecules, thereby changing the hexahydrate coordination solvation structure of zinc and reducing H 2 Activity of O molecules.

[0038] In this embodiment, I +The stabilizer is choline chloride, the hydrogen bond ligand is urea, the zinc salt is zinc sulfate heptahydrate, and the low freezing point hydrogen donor solvent is ethylene glycol. The preparation process of the electrolyte is as follows:

[0039] Step 1: choline chloride, urea, ethylene glycol, and zinc sulfate heptahydrate were mixed in a molar ratio of 1:0.5:5:1.5, heated and stirred at 60° C. for 1 h, and then cooled to room temperature (denoted as DEE15);

[0040] Step 2: Add 50% by volume of deionized water to DEE15 and ultrasonicate for 5 minutes at room temperature to obtain a clear and uniform electrolyte (denoted as HEE50).

[0041] Example 2

[0042] The difference from Example 1 is that in this example, choline chloride, urea, ethylene glycol, and zinc sulfate heptahydrate are mixed in a molar ratio of 1:0.5:5:1, heated and stirred at 65°C for 2h, and then cooled to room temperature (denoted as DEE10), and the remaining steps and parameters are the same as in Example 1.

[0043] Example 3

[0044] The difference from Example 1 is that in this embodiment, choline chloride, urea, ethylene glycol, and zinc sulfate heptahydrate are mixed in a molar ratio of 1:0.5:5:0.5, heated and stirred at 70°C for 2h, and then cooled to room temperature (denoted as DEE05), and the remaining steps and parameters are the same as in Example 1.

[0045] Example 4

[0046] The difference from Example 1 is that in this example, 40% by volume of deionized water is added to DEE15, and ultrasonic treatment is performed at room temperature for 5 minutes to obtain a clear and uniform electrolyte (denoted as HEE40). The remaining steps and parameters are the same as in Example 1.

[0047] Example 5

[0048] The difference from Example 1 is that in this example, deionized water with a volume fraction of 60% is added to DEE15, and ultrasonic treatment is performed at room temperature for 5 minutes to obtain a clear and uniform electrolyte (denoted as HEE60). The remaining steps and parameters are the same as in Example 1.

[0049] Example 6

[0050] The difference from Example 1 is that in this example, choline bromide is used to replace choline chloride, and the remaining steps and parameters are the same as those in Example 1. The obtained electrolyte is recorded as HEE50-Br.

[0051] Example 7

[0052] The difference from Example 1 is that in this example, methanol is used to replace ethylene glycol, and the remaining steps and parameters are the same as those in Example 1. The obtained electrolyte is recorded as HEE50-MeOH.

[0053] Example 8

[0054] The difference from Example 1 is that in this example, propylene glycol is used to replace ethylene glycol, and the remaining steps and parameters are the same as those in Example 1. The obtained electrolyte is recorded as HEE50-Gly.

[0055] Example 9

[0056] This embodiment provides an aqueous zinc-iodine battery, wherein the electrolyte used is the electrolyte in Example 1, and the preparation process is as follows:

[0057] 1. Preparation of positive electrode: Mix activated carbon (AC) and iodine in a mass ratio of 2:1, put into 120mL deionized water, stir at room temperature for 24h for iodine adsorption, then add carbon nanotubes (CNT) and bacterial cellulose (BC) to the above solution, accounting for 10% of the total electrode mass. Ultrasonic treatment for 30min, then vacuum decompression and filtration to obtain AC / I 2 The composite material was vacuum dried at 50°C, and the electrode sheet obtained by drying was cut into discs with a diameter of 12 mm for use as the positive electrode. The loading amount of the active substance iodine was 1 mg cm -2 .

[0058] 2. Preparation of diaphragm: Cut the glass fiber film into discs with a diameter of 16 mm and use them as diaphragms for later use;

[0059] 3. Assemble the battery: Use a CR2032 button-type battery shell, use the prepared electrode sheet as the positive electrode, and a metal zinc sheet (purity ≥ 99.00%) as the negative electrode, add HEE50 electrolyte to completely soak the diaphragm, and finally stack each part tightly in sequence and put it into the button-type shell to complete the assembly of the zinc-iodine full battery.

[0060] Example 10

[0061] The difference from Example 9 is that the electrolyte in Example 6 is used in this example, and the remaining steps and parameters are the same as those in Example 9.

[0062] Embodiment 11

[0063] The difference from Example 9 is that the electrolyte in Example 7 is used in this example, and the remaining steps and parameters are the same as those in Example 9.

[0064] Example 12

[0065] The difference from Example 9 is that the electrolyte in Example 8 is used in this example, and the remaining steps and parameters are the same as those in Example 9.

[0066] Comparative Example 1

[0067] The difference from Example 1 is that in this example, choline chloride, urea, ethylene glycol, and zinc sulfate heptahydrate are mixed in a molar ratio of 1:0.5:5:2, heated and stirred at 60°C for 1 h, and then cooled to room temperature (denoted as DEE20), and the remaining steps and parameters are the same as in Example 1.

[0068] Comparative Example 2

[0069] The difference from Example 1 is that in this example, choline chloride, urea, ethylene glycol, and zinc sulfate heptahydrate are mixed in a molar ratio of 1:0.5:5:2.5, heated and stirred at 60°C for 1 h, and then cooled to room temperature (denoted as DEE25), and the remaining steps and parameters are the same as in Example 1.

[0070] Comparative Example 3

[0071] The difference from Example 9 is that the electrolyte in this comparative example is prepared by directly dissolving zinc sulfate heptahydrate in deionized water to obtain a liquid electrolyte with a zinc sulfate concentration of 2 mol / L. The remaining steps for preparing the battery are the same as those in Example 9.

[0072] Comparative Example 4

[0073] The difference from Example 9 is that the electrolyte in this comparative example is prepared by dissolving zinc sulfate heptahydrate and sodium chloride in deionized water to obtain a liquid electrolyte with a zinc sulfate concentration of 2 mol / L and a sodium chloride concentration of 1 mol / L. The remaining steps for preparing the battery are the same as those in Example 9.

[0074] The following are the relevant experimental measurements and conclusions.

[0075] 1. The relevant experimental results of Examples 1-3 and Comparative Examples 1-2 are shown in Table 1:

[0076]

[0077]

[0078] Table 1

[0079] 2. The performance of the zinc-iodine batteries obtained in Examples 9-12 and Comparative Examples 3-4 was measured:

[0080] Cyclic voltammetry was performed using a Princeton electrochemical workstation in the voltage range of 0.6 to 1.8 V with a scan rate of 0.3 mV s -1The voltage range of the battery was 0.6-1.8V (relative to Zn / Zn 2+ ) in a constant current charge and discharge test, the test current density is 10C under normal temperature conditions. 2 The specific capacity of the battery is calculated based on the mass of iodine.

[0081] Measurement results:

[0082] Figure 1 1 is a charge and discharge curve diagram of the zinc-iodine battery obtained in Example 9 and Example 10. As can be seen from the figure, the zinc-iodine battery based on HEE50-Br at high potential (I 2 / I + ) has a lower voltage platform than that of the zinc-iodine battery based on HEE50.

[0083] Figure 2 The charge and discharge curves of the zinc-iodine battery obtained in Example 9 and Examples 11 and 12 are shown in FIG. As can be seen from the figure, compared with HEE50-MeOH and HEE50-Gly used in Examples 11 and 12, respectively, the discharge specific capacity of the zinc-iodine battery in Example 9 is the highest, thanks to the fast and stable four-electron conversion reaction of iodine.

[0084] Figure 3 The cyclic voltammetry curves of the zinc-iodine battery obtained in Example 9 and Comparative Examples 3 and 4, respectively, wherein the scanning rate is 0.3 mV·s -1 As can be seen from the figure, both Example 9 and Comparative Example 4 show two pairs of redox peaks, while Comparative Example 3 only shows a redox peak at a low potential. In addition, compared with Comparative Example 4, the smaller potential difference in Example 9 demonstrates its excellent reaction kinetics, and the good symmetry of the current response indicates the excellent reversibility of iodine conversion.

[0085] Figure 4 The charge and discharge curves of the zinc-iodine battery obtained in Example 9 and Comparative Examples 3 and 4 are shown. As can be seen from the figure, compared with Comparative Example 3, the zinc-iodine battery obtained in Example 9 has a significantly improved discharge capacity, which is almost twice that of the electrolyte using Comparative Example 3, thanks to the activation of the four-electron conversion reaction of iodine.

[0086] Figure 5 The figure is a cycle performance diagram of the zinc-iodine battery obtained in Example 9 at room temperature and 10C current density. It can be seen from the figure that when the zinc-iodine battery assembled with HEE50 is used to test the electrochemical performance, the capacity can reach 465mAh·g -1 , the Coulomb efficiency basically remained at 100%, and its capacity retention rate was 75.1% after 15,000 cycles.

[0087] Figure 6The figure is a cycle performance diagram of the zinc-iodine battery obtained in comparative example 4 at room temperature and a current density of 10C. It can be seen from the figure that when ZnSO 4 -NaCl-assembled zinc-iodine battery tested its electrochemical performance, with a capacity of 390 mAh g -1 , but the coulombic efficiency is very unstable, and the capacity decays rapidly after 50 cycles. In comparison, the electrolyte in Example 9 achieves a more stable I + The cation reacts with four electrons to undergo reversible transformation.

[0088] Figure 7 , 8 The cycle performance diagrams of the zinc-iodine battery obtained in Example 9 at 40°C, 10C current density and -25°C, 0.5C current density are shown. It can be seen from the figure that the zinc-iodine battery exhibits excellent cycle stability in the temperature range of -25°C to 40°C, which is attributed to the excellent tolerance of the HEE50 electrolyte system to ultra-high and ultra-low temperatures, which greatly broadens the operating temperature range of aqueous zinc-iodine batteries.

[0089] 3. Relevant performance determination of zinc symmetric (Zn||Zn) battery:

[0090] The electrolytes prepared in Examples 1, 4, and 5 were used to assemble Zn||Zn batteries: two polished zinc sheets were used as working electrodes and counter electrodes, HEE40, HEE50, and HEE60 were used as electrolytes, and glass fiber membranes were used as separators to assemble Zn / / Zn symmetrical batteries, and deposition / stripping tests were performed (deposition / stripping current: 5 mA cm -2 ).

[0091] Fig. 9 The figure is a cycle performance diagram of a zinc symmetric battery assembled using the electrolytes in Examples 1, 4 and 5. It can be seen from the figure that, compared with the electrolytes in Examples 4 and 5, the electrolyte in Example 1 has a longer battery cycle life.

[0092] Fig.10 , 11 The long cycle performance diagrams of the Zn||Zn symmetrical battery assembled using the electrolyte in Example 1 at -25°C and 40°C are shown respectively. It can be seen from the figure that even at a high temperature of 40°C, the symmetrical battery assembled using the electrolyte in Example 1 can still operate normally and can be stably cycled for 450 hours. It can also operate normally at a low temperature of -25°C and can be stably cycled for 450 hours. This shows that the electrolyte prepared by the present invention has great tolerance to ambient temperature.

[0093] In summary, the zinc-iodine battery constructed by the present invention can achieve highly reversible I in a wide temperature range of -25°C to 40°C. - / I2 / I + The invention has high conversion and fast iodide conversion kinetics, high energy density and excellent long cycle stability. In addition, due to the unique solvation structure of the electrolyte, the activity of water molecules in the system is reduced, thereby inhibiting the occurrence of hydrogen evolution reaction and other side reactions. Therefore, the present invention provides a feasible strategy for achieving a wide temperature range, high capacity and high performance of zinc-iodine batteries, which has outstanding substantive characteristics and significant progress compared with the prior art.

[0094] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

Claims

1. An electrolyte for an aqueous zinc-iodine battery, characterized in that: byI + The invention is prepared from a stabilizer, a hydrogen bonding ligand, a low freezing point hydrogen donor solvent and a zinc salt, wherein the + The molar ratio of the stabilizer, the hydrogen bonding ligand, the low freezing point hydrogen donor solvent and the zinc salt is 1:0.5:5:0.5-1.

5.

2. The electrolyte of an aqueous zinc-iodine battery according to claim 1, characterized in that: I + The molar ratio of the stabilizer, the hydrogen bonding ligand, the low freezing point hydrogen donor solvent and the zinc salt is 1:0.5:5:1.

5.

3. An electrolyte for an aqueous zinc-iodine battery according to claim 1 or 2, characterized in that: I + The stabilizer is choline chloride or choline bromide.

4. The electrolyte of an aqueous zinc-iodine battery according to claim 3, characterized in that: The hydrogen bonding ligand is urea.

5. The electrolyte of an aqueous zinc-iodine battery according to claim 4, characterized in that: The zinc salt is zinc sulfate heptahydrate.

6. The electrolyte of an aqueous zinc-iodine battery according to claim 5, characterized in that: The low freezing point hydrogen donor solvent is at least one of methanol, ethylene glycol and glycerol.

7. The method for preparing an electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Weigh I according to the proportion + The stabilizer, hydrogen bonding ligand, and zinc salt are placed in a beaker, and a low freezing point hydrogen donor solvent is added to obtain a mixed solution, which is then stirred at 60-70°C for 1-2h and then cooled to room temperature; Step 2: Add 40-60% by volume of deionized water to the mixed solution obtained in step 1, and ultrasonicate at room temperature until the solution is uniform and transparent, thereby obtaining an electrolyte.

8. A wide temperature range, high capacity aqueous zinc-iodine battery, comprising a positive electrode, a negative electrode, and a separator, characterized in that: Also includes the electrolyte according to any one of claims 1 to 6.

9. The aqueous zinc-iodine battery according to claim 8, characterized in that: The positive electrode is a composite material of iodine and activated carbon.

10. The aqueous zinc-iodine battery according to claim 9, characterized in that: The negative electrode of the battery is metallic zinc.

Citation Information

Cited By

  • Precursor solution, quasi-solid electrolyte and preparation method and application of quasi-solid electrolyte

    CN120237282A

  • Strong coordination type electrolyte with simple components and high-surface-capacity four-electron zinc-iodine soft package battery

    CN121460749A